General Anxiety Disorder-Related Coronavirus Disease-19 Outbreak in Indonesia: A Case Report - Wulandari, Patricia; Hidayat, Rachmat (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The outbreak of coronavirus disease-19 (COVID-19) which is now a pandemic has become a problem that occurs in every area of life. Coronaphobia, a new term in the psychiatry literature referring to excessive fear of being infected by SARS-COV2 or COVID 19. Infected by influenza, having close relatives or friends with this fatal virus, and strong fear of infection have been reported as important predictors of stress posttrauma. We report a case report-related COVID-19 in Indonesia. CASE PRESENTATION: A 23-year-old female, dentistry student living in a boarding house in East Java, Indonesia, along with her friend and coming from a middle-up income family background, came to psychiatric consultation with complaints of difficulty of breathing for 1 month ago. This anxiety began to get heavy, especially since the severe acute respiratory syndrome coronavirus 2 (COVID 19) outbreak appeared in Indonesia. In addition, she also recently experienced a failure in her final examination so that her study period as a dentistry student must be extended. Exploration of history revealed that the patient initially experience a feeling of heaviness in the chest, difficulty breathing, palpitation, and sometimes feeling sad due to her failure before. She was then given pharmacological interventions in the form of fluoxetine and clobazam and psychotherapy and progressive muscular relaxation through online. CONCLUSION: General anxiety disorder, especially due to the COVID-19 outbreak, should be managed appropriately and comprehensively. The pandemic situation and widespread spread of the disease cause psychotherapy to be modified in such a way that assistance can be carried out online.